Programas de educação profissional na APAE de Toledo Paraná. - Johann, Jackson (2011)
In the present work we study the Professional Education Programs which are part of the Process of Professional Education and Placement in the Workplace (PECT) of the APAE of Toledo, Paraná, in the decade of 1990. We intend to apprehend the Professional Education programs based on the discourse of valorization of qualification for the formation of workers with autonomy, creativity, cooperation, responsibility, etc., once these qualities are imperative to the new methods of capitalist organization of production. In that sense, the exposition of this work contemplates, in the first chapter, a brief retrospective of the history of Special Education, aiming to demonstrate the begining of educational services to people with disabilities, highlighting the emergence of the Association of Parents and Friends of Exceptional Children (APAE) and, consequently, of the National Federation of APAEs (FENAPAES). In the second chapter, we present some considerations on the demands for the worker in the decade of 1990, as from the process of productive restructuring of the capital, situating, in this debate, the problematic of people with disabilities, as well as the legal bases of Brazilian Professional Education for the person with disability. As for the third chapter, we approach the PECT programs of the APAE of Toledo, Paraná, from the reconstitution of the institution‟s history. We found that since 1998, 2,198 students with disabilities have taken part in the PECT programs, and that until the end of 2010, 34 students were inserted in the labor market.